Facet effects on bimetallic ZnSn hydroxide microcrystals for selective electrochemical CO2 reduction - Liu Han; Cheng-wei Wang; Shan-shan Luo; Ying-tang Zhou; Bing Li; Ming Liu (Green Energy & Environment, 2024)
Employing crystal facets to regulate the catalytic properties in electrocatalytic carbon dioxide reduction reaction (eCO2RR) has been well demonstrated on electrocatalysts containing single metals but rarely explored for bimetallic systems. Here, we synthesize ZnSn(OH)6 (ZSO) microcrystals (MCs) with distinct facets and investigate the facet effects in eCO2RR. Electrochemical studies and in situ Fourier Transform Infrared Spectroscopy (in situ-FTIR) reveal that ZSO MCs produce mainly C1 products of HCOOH and CO. The {111} facet of the ZSO MCS exhibits higher selectivity and faradaic efficiency (FE) than that of the {100} facet over a wide range of potentials (−0.9 V ∼ −1.3 V versus RHE). Density Functional Theory (DFT) calculations elucidate that the {111} facet is favorable to the adsorption/activation of CO2 molecules, the formation of intermediate in the rate-determining step, and the desorption of C1 products of CO and HCOOH molecules.